Capital Formation, Foreign Aid, Human Capital Development and Economic Growth in Nepal - Lamichhane, Pitambar; Dhungel, Bashu Dev; Shrestha, Purna Man (Nepal Journal of Multidisciplinary Research, 2025)
Background: Capital formation and foreign aid provide funds for the investment in developing countries for infrastructure development and acceleration economic progress. Educated, skillful and healthy human capital plays a vital role for the long-run economic development. Therefore, this paper aims to investigate the effect of capital formation, foreign aid and human capital development on economic growth in Nepal. Methods: This study applies ordinary least square modeling based on causal research design for the examination of impact of gross fixed capital formation (GFCF), foreign aid such as foreign grants (GRANT), foreign debt (DEBT), World Bank debt (WBD) and human capital development (HCD) on economic growth. Gross domestic per capita (GDPPC) is considered as economic growth and GFCF, GRANT, foreign DEBT, WBD and secondary school enrolment as HCD are considered as explanatory variables. Results: This study reveals capital formation has dominant role in economic growth and Nepalese government needs to focus on sufficient capital formation for the acceleration of rapid economic development. This paper explores foreign aid that plays significant role in bridging deficit budget and accelerates economic development. Government needs to use foreign aid for infrastructure development and rapid economic growth. However, secondary school enrolment as HCD does not have imperative positive influence because secondary education has expanded only in numbers but lack of quality, knowledge, skills to meet job market needs, more migration for low skill works and policy weakness of human capital development are the reasons of unexpected effect on economic growth in Nepal. Conclusion: This study concludes capital formation and foreign aid have leading role for economic growth. Nepalese policy makers, government and bureaucrats need to emphasize to articulate and implement various policies for formulation of more capital and optimum utilization of foreign aid for the rapid acceleration of economic development. Policy maker should formulate human capital polity emphasizing in improving education quality, knowledge, skills to meet market needs via fostering innovation, integrating digital skills, retaining talent human resources to accelerate productivity for rapid economic growth. Novelty: The novelty of this paper is integrated approach to examine combined effect of capital formation, foreign aid and human capital development on economic growth. This study unifies drivers of economic development within a single framework via holistic approach for achieving inclusive and sustainable economic development.